The Role of Public Servants in Alleviating Poverty in Indonesia - Susilawati Susilawati (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
Poverty remains a persistent issue in Indonesia, and it requires the involvement of various actors, including public servants. This study aims to explore the role of public servants in alleviating poverty in Indonesia. To achieve this goal, a qualitative research method was employed, and data was collected through semi-structured interviews with public servants who work in poverty-alleviation programs. The study found that public servants play a crucial role in poverty reduction efforts by providing access to basic services, including health care and education, and implementing poverty-alleviation programs. However, there are several challenges that public servants face, such as limited resources and bureaucratic obstacles, which hinder their ability to deliver effective services. In conclusion, this study highlights the importance of public servants in poverty reduction efforts and suggests the need for greater support and resources to enable public servants to deliver better services and improve the lives of people living in poverty.